INTEGRASI HUKUM ISLAM DAN HUKUM ADAT DALAM PEWARISAN MASYARAKAT BUGIS BONE (Studi Di Kecamatan Palakka) - zubair, asni (AL-RISALAH, 2016)
Integration of Islamic law and customary law of inheritance that run in the Bugis community in District Palakka Bone takes place in the form of assimilation, syncretic, acculturative, and legitimacy. Integration in a syncretic form can be seen in the division of inheritance society that make Islamic law and customary law as a reference. Integration in the form acculturative can be seen at the time of the division of property, there is executed before the death, and there is also carried out after the death of the testator.